Aptidão, evolução e conflitos de uso das terras no município de Itaara, RS - Poelking, Everton Luís (2007)
The landscape is constantly altered by the man's action. The rational use of the natural resources and space it should be done in agreement with the natural vocation of the environment. For so much it is necessary the knowledge of the environmental attributes for a efficient planning of use. The purpose of this work was make the survey of the environmental attributes like soil, relief, landcovering and land use for monitoring as well as detection of problems related to use. Being used Geografic Information Sistems techniques in the generation of PIs of soils, steepness, APPs , land suitability and evolution of the land covering from 1987 to 2006, were identified the environmental attributes of the Itaara county, with use of satellite images and topographical maps. For the crossing of those PIs the map of use adaptation was elaborated for identification of land use conflicts. About 33,5% of the area of the Itaara county were found formed by Entisol, concentrated in the areas of larger steepness. Approximately 55% of their lands with restricted land suitability, being the remaining just for capable to forestry. It was verified that Itaara still preserves part of his original forest, mainly in the areas more slope and of more shallow soils. The total area with APPs in Itaara is 2929 ha. The land use of the farmers, along that period, was adapting to the adequate land suitability and the environmental legislation, protecting the areas of the plateau for agricultural activity. However some areas are being used with activities above his natural aptitude, mainly in places with accentuated steepness and shallow and stony soils, besides places destined to APPs, being explored with agriculture or pasture. The use of Geografic Information Sistem came as excellent tool to aid in the rising, organization, crossing and edition of the information regarding the environmental attributes in the generation of the adaptation proposal and detection of conflicts of lands cover